O estudo das propriedades mecânicas e elétricas da liga al-1%si com adição de nanotubos de carbono de paredes múltiplas - ALMEIDA, Anderson Pereira de (2023)
The class of composites allows a wider range of properties. Thus, the sum of the singularities of a eutectic Al–Si alloy and multi-walled carbon nanotubes, thermally treated, was made in order to produce a new type of heat-resistant material. From the raman spectrum of the nanotubes used, a low purity of these was seen, in view of the presentation of an ID/IG ratio of 0.94. The formulation Al-1%Si+0.05%NTCPM (TT), showed a great grain refinement in its macrostructure. As a result, the hardness was impacted, showing a gain close to 100% in the Vickers microhardness test. The nanocomposite had the general characteristic of a ductile material, this was proven from the tensile test and the data derived from it. The fractographs approve the ductile characteristic, with the presence of the fracture mechanism by microcavities (Dimples), a fracture surface with a lot of deformation and a difference of almost 25% in the size of the fracture surface. The thermoresistivity test related mechanical resistance and electrical conductivity data, proving that the Nanocomposite is not a thermoresistant material.